Fabrication of TiO2 Nanoparticles Slab Waveguide by Spin-coating Method with 2-Propanol Solvent - Lucky Putri Rahayu; Yono Hadi Pramono; Asnawi Asnawi; Gatut Yudoyono (IPTEK Journal of Science, 2017)
The slab waveguide TiO2 nanoparticles by spin-coating method was fabricated with solvent 2-propanol. Component of TiO2 phase anatase is obtained using the old method of coprecipitation with time stirring 5 h. The Slab waveguide fabrication process using the spin-coating method with a rotation speed of 3000 rpm for 60 s and thermally treated at 100 0C for 15 min. Heating temperature used should be higher than the boiling point of the solvent (2-propanol) is 82.2 0C. This research was intended to determine the thickness of the film of the waveguides that have been fabricated and examination absorbance and transmittance. From the test results of absorbance and transmittance using UV-Vis known that the highest absorption (262 nm) and average transmittance (91%). The thickness of the film obtained 131.6 μm